The effect of ketamine on the separation anxiety and emergence agitation in children undergoing brief ophthalmic surgery under desflurane general anesthesia - Jeong, Won Ju (The Korean Society of Anesthesiologists, 2012)
BACKGROUND: Emergence agitation (EA) frequently occurs after desflurane anesthesia in children. Ketamine, because of its sedative and analgesic properties, might be useful for the management of separation anxiety and EA. We investigated the preventive effect of ketamine on separation anxiety and EA after desflurane anesthesia in children for brief ophthalmic surgery. METHODS: Sixty children, ranging in age from 2-8 years old, undergoing brief ophthalmic surgery were randomly allocated to one of the 3 groups: group C received normal saline, group K1.0 received ketamine 1.0 mg/kg intravenously before entering the operating room, or group K0.5 received ketamine 0.5 mg/kg 10 min before the end of the surgery. Before induction, the separation anxiety score was evaluated. Extubation time, post-anesthesia care unit stay time, postoperative nausea and vomiting, emergence agitation, and pain were assessed. RESULTS: The group K1.0 had a lower separation anxiety score compared with groups K0.5 and C. Extubation time in group K0.5 was significantly prolonged compared with groups K1.0 and C. The incidence of EA and the modified Children's Hospital of Eastern Ontario Pain Scale were significantly lower in group K1.0 and group K0.5 compared to group C, but there was no significant difference between groups K1.0 and K0.5. CONCLUSIONS: In children undergoing brief ophthalmic surgery with desflurane anesthesia, ketamine 1.0 mg/kg administered before entering the operating room reduced separation anxiety, postoperative pain, and incidence of EA without delay in recovery.